GPER1 is involved in shaping tumor immune microenvironment and its expression is decreased in NSCLC tumorigenesis - Zhenhua Li; Chao Xie; Jingjing Cui; Hui Xu; Dingbiao Li (Scientific Reports)
Abstract G-protein coupled estrogen receptor 1 (GPER1) is involved in estrogen response and associated with tumorigenesis in several solid tumors, and we previously reported that its positive expression rate is more than 80% in lung cancer. However, GPER1 has been less studied during the tumorigenesis in non-small cell lung cancer (NSCLC). We used Lung Adenocarcinoma (LUAD) and Lung Squamous Cell Carcinoma (LUSC) data from the Cancer Genome Atlas and Gene Expression Omnibus databases, and self-sequencing data of whole transcriptome of A549 cells for research. Firstly, the expression of GPER1 in adjacent tissues and cancer tissues was compared. Then, according to the median of GPER1, LUAD and LUSC samples in the data set were assigned into GPER1 high and low expression group, respectively. The hub genes were enriched and analyzed. Additionally, the association between GPER1 expression and immune related responses were explored. We obtained GPER1-inhibited and -activated differentially expressed genes (DEGs) from the self-sequencing data. Finally, the GPER1-related competitive endogenous RNA (ceRNA) network was constructed and verified by experiments. The expression of GPER1 in cancer tissues was decreased when compared with that in healthy tissues. The GPER1 gene has good diagnostic value as a differentiator between cancer and normal samples in LUAD- and LUSC-related datasets. Fourteen and thirteen hub genes were identified in LUAD and LUSC, respectively. They were all enriched in the pathways of actin cytoskeleton regulation, extracellular matrix assembly, PI3K-Akt signaling pathway. In addition, GPER1 was significantly associated with immune cells infiltration and expression of common immune checkpoints, and its low expression could predict benefit from immune checkpoint blockade (ICB) treatment in LUSC. The whole-transcriptome sequencing data of A549 cells were analyzed to obtain 132 GPER1 repression- and 39 GPER1 activation-related mRNA, and 13 hub genes were finally screened. Further, the GPER1-related transcription factor (TF)-miRNA–mRNA network and lncRNA/circRNA–miRNA–mRNA ceRNA networks were constructed. Finally, confirmatory studies demonstrated that the hub genes and MAPK signaling pathway were regulated by GPER1, and knockdown of GPER1 expression caused F-actin cytoskeleton rearrangement and promoted cell migration in A549 cells. The expression of GPER1 was decreased during the tumorigenesis in NSCLC. GPER1 was significantly associated with immune cells infiltration and immune checkpoints expression in both LUAD and LUSC, and its low expression could predict benefit from ICB treatment in LUSC. In addition, we report a ceRNA network that may provide new insight into the roles of GPER1 in NSCLC development.